Experiences Of Sexual Abuse Is Related To Life Time Diagnosis Of Mental Disorder: A Systematic Review - Dr. Syeda Razia Bukhari; Ms. Azra Batool; Ms. Shazia Ismail; Ms. Ifra Tashfeen (Kurdish Studies, 2024)
Objective: The objective of this systematic review is to assess the comprehensive analysis of the correlation between lifetime diagnosis of various mental diseases and experiences of sexual abuse Methods: The systematic review was taken by screening last ten years (2013 - 2023) articles related to sexual abuse and related various mental health disorders, which are conducted on sexual abuse victims. Results: The compilation of (n=10) data from the last ten years shows more prevalence of mental health issues in sexual abuse in females than males. Conclusion: It is concluded that there is a need for more research to fully understand effective treatment to reduce the vulnerability and risk of sexual abuse and related mental health disorders.